Ökologisch, Solidarisch, Unverkäuflich. Das Modellprojekt "Bikes and Rails" verbindet leistbare Mieten mit ökologischer Verantwortung. - Laimer, Christoph; Rauth, Elke (Forum Landschaftsplanung - AbsolventInnenverband, 2020)
"Bikes and Rails" is part of the habiTAT Tenement Houses Syndicate, a network of in solidarity working self-organised housing projects in Austria with the aim to withdraw houses from the real estate market and save the right to housing. Due to the specific organization and financing model, residents do not necessarily need their own funds and rents remain affordable in the long term. In Vienna´s urban development area Sonnenwendviertel-Ost, "Bikes and Rails" has built a low energy paaive house using a timber frame construction with 18 apartments, common spaces, a neighbourhood café and a socio-economic bike workshop combining ecological, social and economic sustainability.
Keywords: Modellprojekt; Kollektivhaus; Kollektivwohnform; Nachhaltiges Bauen; Selbstorganisation; Finanzierungsmodell; Alternatives Bauen; Passivhaus